2016
DOI: 10.1039/c6ra00360e
|View full text |Cite
|
Sign up to set email alerts
|

Pickering emulsions stabilized by shape-controlled silica microrods

Abstract: Silica microrods with varying aspect ratios but similar surface characteristics are synthesized and their potential in preparing stable oil-in-water Pickering emulsions are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…The Pt-containing Janus catalyst not only showed excellent interfacial activity for stabilizing Pickering emulsions, but also enhanced reaction efficiency in the biphasic nitroarene hydrogenation reaction. 27 With the development of new synthesis techniques, various non-spherical particles have now been produced and tested as colloidal surfactants, including particles shaped as onedimensional fibers, 46,47 ellipsoids, 34 rods, [48][49][50][51] two-dimensional nanosheets 28,52 or plates. 4 Huang et al prepared silica microrods with aspect ratios (AR, ratio of long to short axis) varying from 1 to 16 ( Figure 2f) to stabilize hexadecane/water emulsions and found that the microrods with larger ARs exhibited superior stabilization efficiency, attributing this to their higher steric hindrance, interface adsorption energy and stronger capillary forces.…”
Section: Particle Geometrymentioning
confidence: 99%
“…The Pt-containing Janus catalyst not only showed excellent interfacial activity for stabilizing Pickering emulsions, but also enhanced reaction efficiency in the biphasic nitroarene hydrogenation reaction. 27 With the development of new synthesis techniques, various non-spherical particles have now been produced and tested as colloidal surfactants, including particles shaped as onedimensional fibers, 46,47 ellipsoids, 34 rods, [48][49][50][51] two-dimensional nanosheets 28,52 or plates. 4 Huang et al prepared silica microrods with aspect ratios (AR, ratio of long to short axis) varying from 1 to 16 ( Figure 2f) to stabilize hexadecane/water emulsions and found that the microrods with larger ARs exhibited superior stabilization efficiency, attributing this to their higher steric hindrance, interface adsorption energy and stronger capillary forces.…”
Section: Particle Geometrymentioning
confidence: 99%
“…Finally we emphasize that the segregation behavior predicted by our simulations can in principle be verified in experiments using smectic shells of molecular crystals [49][50][51][52][53][54][55][56][57][58] or Pickering emulsion droplets covered with rod-like colloids [59][60][61][62][63][64] . Another option are layers of silica rods which are recently studied under various constraints 65,66 , aspherical surfactants 67 or ellipsoidal colloids bound to curved fluid-fluid interfaces 68 .…”
Section: Discussionmentioning
confidence: 76%
“…Long term stabilization of emulsions in cases where the coverage C is low has been reported in several cases for both o/w and w/o emulsions. 61 63 More recently, 64 o/w emulsions exhibiting low surface coverage of rod-shaped cellulose particles has been reported. Depending on the rod length, C values between 44% and 84% were found to be required for emulsion stabilization.…”
Section: Resultsmentioning
confidence: 99%